2010
DOI: 10.1016/j.compscitech.2010.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of silica fillers on the ageing by gamma radiation of EDPM nanocomposites

Abstract: Abstract:This study evidences that the presence of silica fillers as well as their surface treatment influences the impact of gamma irradiation on the mechanical properties of the filled materials. It influences it both chemically, by a modification of the kinetics of the degradation reactions, and physically, through the complex modification of the filler-filler and fillermatrix interactions involved in the mechanical properties of the filler network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 18 publications
2
33
0
Order By: Relevance
“…As reported in reference,17 because the polymer phase of this composite is less crosslinked, irradiation at 25 °C, leads also to a slight crosslinking phenomenon at the beginning of irradiation. However, after 50 kGy, the main occurring process is chain scission.…”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…As reported in reference,17 because the polymer phase of this composite is less crosslinked, irradiation at 25 °C, leads also to a slight crosslinking phenomenon at the beginning of irradiation. However, after 50 kGy, the main occurring process is chain scission.…”
Section: Resultssupporting
confidence: 68%
“…The curing time ( t 98 at 170 °C) is previously estimated from torque measurement performed with a MOSANTO analyzer; it is the time needed to obtain 98% of the maximum torque; it is chosen equal to 10 min for unfilled EPDM and ATH‐filled EPDM, and to 5 min for silica‐filled EPDM. In the previous study,17 it has been shown that the polymer phase of this composite is slightly less crosslinked than the unfilled material.…”
Section: Methodsmentioning
confidence: 72%
See 3 more Smart Citations